Beanie Boos : ultimate collector's guide - Rusu, Meredith (New York : Scholastic Inc., 2018)
They're cuddly, they're cute -- they're the Beanie Boos! This collector's guide is packed with quirky tidbits on all 200+ plush Beanie Boo collectibles, even rare limited editions.
Keywords: Toys -- Collectors and collecting -- Juvenile literature; Collectors and collecting -- Juvenile literature